La façon virile de Montaigne - Bruno Méniel (Itinéraires, 2008)
The concept of virility is fundamental to understanding the ethics of the Essais, since it allows the articulation of the social ideal of a warrior nobility and a moral ideal of virtue and vigour, as well as a stylistic ideal of naturalness and the primacy of subject matter, which links Montaigne to Seneca and Erasmus. At the same time, this ethics, which has affinities with Stoicism, is undermined by a profound sense of human wretchedness, weakness and inconstancy, which is related to Scepticism.